Development of High-Performance Concrete with Advanced Materials for Sustainable Building Applications - Kandou, Carter; Tumpu, Miswar; Kabo, Don R. G.; Tumengkol, Herman (Engineering, Technology & Applied Science Research, 2025)
Developing High-Performance Concrete (HPC) with advanced materials is crucial for achieving superior concrete that aligns with sustainable building practices. The use of innovative materials enhances both fresh and hardened properties, offering improved workability and strength. This study explores the impact of incorporating advanced materials into concrete mixtures by evaluating the performance of different compositions. Three mix variations were prepared by adjusting the types and dosages of admixtures. The first mix used a conventional Type F superplasticizer, while the other two applied advanced materials at varying dosages. Slump tests were conducted on fresh concrete and cylindrical specimens (10x20 cm) were tested to measure unit weight and compressive strength after 7, 14, and 28 days. Results indicate that the use of advanced materials significantly improves concrete performance, even at lower dosages compared to traditional superplasticizers. This research confirms that incorporating advanced materials improves both workability and compressive strength of concrete. The findings suggest that these materials offer a sustainable solution for developing high-performance concrete with enhanced durability and reduced material consumption. Consequently, their integration in construction can contribute to more sustainable, efficient, and resilient building structures. Further research is recommended to explore the long-term effects of advanced materials on concrete performance under various environmental conditions. The study highlights the potential of advanced material technologies as a transformative approach in concrete quality management within the construction industry.